1979
DOI: 10.1084/jem.149.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Role of marrow-derived monocytes and mesangial cells in removal of immune complexes from renal glomeruli.

Abstract: Intravenously administered antigen-antibody complexes or protein aggregates localize in the glomerular mesangium. The mechanism of removal of these deposited substances has been difficult to study. Based on observations that particulates such as ferritin (1) and silver-protein aggregates (2) were found within lyososomes, mesangial cells were concluded to be phagocytic and therefore to participate in the clearing of immune complexes and aggregated IgG from the mesangium. In studies with injection of preformed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…Both vascular volume (23) and preexisting glomerular damage (24) may be determinants of IC uptake. Intrarenal deposition of localized IC appears to be a function of the phagocytic mononuclear cells in the mesangium (25).…”
Section: Discussionmentioning
confidence: 99%
“…Both vascular volume (23) and preexisting glomerular damage (24) may be determinants of IC uptake. Intrarenal deposition of localized IC appears to be a function of the phagocytic mononuclear cells in the mesangium (25).…”
Section: Discussionmentioning
confidence: 99%
“…Complement-generated chemotactins and/or Fc receptor interactions with glomerular deposits of immunoglobulins may be involved (Striker, Mannik & Tung, 1979;Holdsworth, 1983). The local expression of cell-mediated immunily has also been implicated in the perpetuation of glomerular inflammation in proliferative immune complex glomeruionephritis (Bhan et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…3,25 Whether phagocytosis of antigen-antibody complexes was induced in mesangial cells was examined in Chediak-Higashi mice, using BMT. This study found that the complexes were principally taken up by cells containing giant lysozomes, 26 suggesting that macrophages derived from the Chediak-Higashi bone marrow donor were the principal phagocytic cells in the mesangial region.…”
mentioning
confidence: 91%